Significant characteristics of scheduled and condition-based maintenance in office buildings - Au-Yong, C.P.; Ali, A.S.; Ahmad, F. (American Society of Civil Engineers, 2014)
Sustainability of buildings is one of the main aims in the construction industry. In achieving sustainability, maintenance of buildings and its facilities, which include planning, implementation, and outcome of maintenance activities, becomes an important criterion. This paper aims to identify the significant characteristics of scheduled and condition-based maintenance in office buildings through reviews of relevant literature and a questionnaire survey. The significance of the characteristics was identified through ranking analysis. A semistructured interview was conducted to obtain further details on the characteristics and measures to enhance efficiency of the characteristics. The findings reveal that the dominant characteristics for scheduled maintenance include quality of spare part and material, the level of labor skill and knowledge, and budget allocation for maintenance labor, whereas for condition-based maintenance, the dominant characteristics are the level of manager skill and knowledge, reliability of maintenance data, and financial allocation for the maintenance manager. The study concludes that these dominant characteristics should be considered in the implementation of maintenance strategies.